Fungsi Partai Politik dalam Memberikan Pendidikan Politik Bagi Masyarakat - Masriyani Masriyani; Herma Yanti (Universitas Batanghari Jambi, 2019)
Democracy is a government by the people, which is interpreted as the most basic. as stipulated in article 28 of the 1945 Constitution, which states that: